TELEPON SELULER DALAM PERSPEKTIF ISLAM - A.Nur Aisyah Rusnali (Al-Din: Jurnal Dakwah dan Sosial Keagamaan, 2019)
Abstract The development of communication technology is now progressing day by day. Not surprisingly, if the use of communication technology seems to be a basic need for every human being on this earth. One form of communication technology development that is increasingly fast is cellular phones. Cellular telephone companies both from within and outside the country increasingly compete to produce cellular phones with good quality and lower prices. This is certainly more tempting for consumers. In addition, cell phones are now not only limited to calling and sending short messages, but the social media features are increasingly attractive and curious for every user. In Islam, technological development has actually been explained in the Qur'an surah Yunus / 101, then in QS. An-Naml / 40 which contains information, and there are many more verses in the Koran that explain the development of technology. When we use it wisely, Islam also views this handphone as very useful because it facilitates difficulties when interacting with the environment and surrounding communities. However, if this cellphone is used poorly, then Islam will view that handphone has many disadvantages and can plunge the user into immorality which of course is not desired by Islam itself. Kata Kunci: telepon seluler; perspektif Islam